Comparing the German and Japanese nursing home sectors: Implications of demographic and policy differences - Alexander Karmann; Shinya Sugawara (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2022)
This research provides a comparative study of the Japanese and German nursing home sectors. Faced with aging populations, both countries share similar long-term care policies based on social insurance. However, descriptive statistics indicate significant differences in the outcomes and costs in their respective nursing home sectors. This research aims to identify the reasons for this state of affairs by examining demographic and policy differences between the two countries. To shed light on the subject from multiple angles, we conduct three types of empirical analysis - regression, the Blinder-Oaxaca decomposition, and data envelopment analysis - on regional data from the past decade. Our findings indicate that the different outcomes are driven by both demographic and policy differences where policy relates to long-term care as well as to additional welfare aid. In terms of policy, a key difference is found in the designs of the welfare programs for low-income elders. In Germany, our results are consistent with moral hazard due to the generous design of the welfare program, while in Japan, our results do not indicate moral hazard, which may be due to strict nursing home admission rules for welfare recipients.
urn:nbn:de:bsz:14-qucosa2-796503
Keywords: I13; I18; J14; 330; Japanese and German nursing home sectors; long-term care insurance; Blinder-Oaxaca decomposition; comparative study; moral hazard; welfare policy